Bedah Logo Autocillin Menggunakan Teori Semiotika - Wulandari, Sari (Humaniora, 2010)
When a brand will communicate with people through visual media, then a visual communication designer will act as the sender in meaningful visual. A vehicle product assurance, Autocillin, will launch its brand; therefore it needs to presence visual identity of Autocillin, which is able to change people?s perception about assurance and also to represent brand image according to its ideals and hopes with its philosophy. Research method uses theory approach of semiotic theory from Peirce with its developing on icon, index and symbol. It also uses semiotic theory from Charles Morris of its semiotic processes: syntax, semantic, and pragmatic; and Roland Barthes approach of semiotic analysis towards design. It will be concluded that through visual identity, Autocillin could answer needs in communicating unprecedented experience of its consumers and change people?s perception of vehicle assurance. Through sign approach, Autocillin is ready to interact and compete with other brands.